URBAN SUFISM: A CASE STUDY OF TASAWUF PRACTICES IN THE UICCI STUDENTS OF SULAIMANIYAH CIPUTAT - Muhammad Akmal Falah (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2019)
The phenomenon of the emergence of a higher interest in studying religious knowledge with a spiritual path began to develop in society. This cannot be separated from the role of the tarekat in the midst of urban life. People in urban areas who study religious knowledge and learn about Sufism in urban areas are then better known as